The effect of Increasing Periods of Drought on The Growth and Development of Two Cultivars of Wheat: - Shakir, Walaa Mahmood (Journal of agricultural, environmental and veterinary sciences, 2022)
The experiment was carried out during the 2018-2019 agricultural season in the plant house of the College of Education for Pure Sciences/University of Diyala, This study was conducted to evaluate the effects of different of irrigation periods on the growth and development of two types of wheat, a(CRD)was used with three replications, the averages were compared at a probability level of 0.05.The study included exposure of two cultivars of Italian and Shami wheat to different irrigation periods 4,8,12,16 and 20days. The results showed that the studied traits were affected by the increase in irrigation periods. Maximum reduction was observed by using 20day irrigation plant heigh, leaf area, dry weight of the vegetative total and yield at a rate of 14.3cm,6.4cm2,1.35g.plant-1,0.49g.plant-1, respectively. While the content of leaves of chlorophyll and the percentage of protein and carbohydrates in the grains increased at the same treatment rate of 0.99mg/g,12.72%,79.99% respectively. The Italian wheat cultivar showed drought tolerance in most of the studied traits, while the cultivar Shami wheat prevailed in plant yield, carbohydrate percentage, and did not differ in the chlorophyll content of leaves.
Keywords: Wheat Varieties; Irrigation Periods; Water Stress; Field Crops; Drought